Stereotypes Surrounding the Hungarian Peasantry During the Years of the First World War - Csíki, Tamás (Ethnographica et Folkloristica Carpathica, 2020)
The paper examines the use and political, ideological, and social meanings of the term peasant and its synonyms. It reflects on how these meanings were modified as a consequence of the structural and experiential changes in the social situation of the agrarian population. The textual analysis is based on publications from the press during the First World War and, thus, the concepts, in their contexts, can be understood first as instruments for propaganda and mental mobilization, that is to say, as political action. Second, these notions and concepts also incorporated past (historical) phenomena and future expectations, through which they offered arguments for programs and ideas to transform society. Third, the texts frequently prompted debates in the media, which strengthened the discursive nature of the press, the controlled publicity, and the usage of vocabulary and language. By the same token, they can also represent a chance to examine the social stereotypes and the experience of personal relations crystallized in these texts.